subject
Mathematics, 04.01.2021 22:20 clewis57

Given: -3(x - 6) + 4(x + 1) = 7x - 14 Step 1: -3x + 18 + 4x + 4 = 7x - 14
Step 2: -3x + 4x + 18 + 4 = 7x - 14
Step 3: 1x + 22 = 7x - 14
Step 4: 1x - 1x + 22 = 7x - 1x - 14
Step 5: 22 = 6x - 14
I need help with this I am confused!?

ansver
Answers: 1

Another question on Mathematics

question
Mathematics, 21.06.2019 18:00
Which represents the solution set of the inequality 5x-9 < 21? a. x < 12/5 b. x > 12/5 c. x > 6 d. x < 6
Answers: 2
question
Mathematics, 22.06.2019 00:30
Bocephus has a bag full of nickels and dimes. if there are 3 times as many dimes as nickels, and he has $\$36.05$ in his bag, how many nickels does he have?
Answers: 1
question
Mathematics, 22.06.2019 02:00
Are you guys willing to me with these last 8 questions on my homework for math reply to this question that i posted
Answers: 1
question
Mathematics, 22.06.2019 04:00
Angle 1 and angle 2 are a linear pair . m angle 1 =x-39 and m angle 2 =x+61 find the measure of each angle
Answers: 1
You know the right answer?
Given: -3(x - 6) + 4(x + 1) = 7x - 14 Step 1: -3x + 18 + 4x + 4 = 7x - 14
Step 2: -3x + 4x +...
Questions
question
Mathematics, 20.08.2019 10:50
question
History, 20.08.2019 10:50
question
Mathematics, 20.08.2019 10:50
question
Chemistry, 20.08.2019 11:00
Questions on the website: 13722361